De las cartas oficiales al rumor. La comunicación de los terremotos en la Monarquía Hispánica (siglo XVII) - Gennaro Varriale (Nuevo mundo - Mundos Nuevos, 2022)
During the Early Modern period, the earthquakes become a topic of interest. The article focuses on the news about the seismic activity of the Hispanic Monarchy. Besides the introduction and conclusions, the essay presents two paragraphs. While the first part scrutinizes the confidential communication by the Habsburg administration, instead, the second analyses public discussions on several disasters, that take place in the streets of Madrid during the summer of 1688.